The Analysis of Renewable Energy Management to Generate Electricity in Lampung Province Indonesia - Redaputri, Appin Purisky; Barusman, M. Yusuf S. (International Journal of Energy Economics and Policy, 2021)
Electricity installed in Lampung is still a power plant with fossil fuels such as steam power plants, diesel power plants, gas engine power plants, and gas power plants. For this reason, it is necessary to make a revolution in the use of fuel in Indonesia, especially in Lampung, by reducing the use of fossil fuels and increasing the use of new fuels or renewable energy. Renewable energy sources are energy sources that are produced from sustainable energy resources if managed properly, including geothermal, wind, bio-energy, sunlight, water flows, and falls, as well as movement and differences in sea layer temperature. Lampung Province itself has a lot of potential renewable energy. With the existing potential, to preserve the environment, it is necessary to increase electricity production using renewable energy. The minimum addition from the current one is 50% for fossil energy and 50% for renewable energy. However, the existing obstacles need to be resolved with the support of the Government and the general public. So that in the future electricity production can increasingly focus on the use of renewable energy. Keywords: Energy Management, Renewable Energy, Electricity JEL Classifications: Q2, Q40, Q42 DOI: https://doi.org/10.32479/ijeep.11549